Aulopus chirichignoae, a new flagfin from the eastern Pacific Ocean (Teleostei, Aulopiformes, Aulopidae) - Béarez, Philippe; Zavalaga, Fabiola; Miranda, Junior; Mennesson, Marion I.; Campos-León, Sarita; Jiménez-Prado, Pedro (Zootaxa, 2024)
A new species of the Aulopidae is described from the waters of southern Ecuador and northern Peru. Aulopus chirichignoae sp. nov. was previously confused with Aulopus bajacali Parin & Kotlyar, 1984, but it differs from this species by a significantly marked elongation of the dorsal fin rays in males (absent in females), a smaller head, modal differences in dorsal and anal ray counts (15 vs 14 and 11 vs 12, respectively), a higher number of vertebrae (50–51 vs 47–49), and color differences, especially on the dorsal fin. DNA barcoding analysis supported the status of new species, evidencing a 4.2% and 2.8% divergence with Aulopus filamentosus (Bloch, 1792) and A. bajacali, respectively. A sequence of an Aulopus sp., collected in the Tropical Eastern Pacific, matches the new species with only a 0.4% divergence, indicating that Aulopus chirichignoae sp. nov. is distributed at least as far north as the Paramount Seamount at 3°20.35’N, ca. 400 km north of the Galápagos Islands.